HUBUNGAN HARGA DIRI DENGAN GEJALA NARSISTIK (NARCISSTIC PERSONALITY DISORDER) PADA MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER UNIVERSITAS MALAHAYATI - Rahma Elliya; Ainur Rahma (Malahayati Nursing Journal, 2020)
ABSTRACT: THE CORRELATION OF SELF-ESTEEM TO NARCISTIC SYMPTOM (NARCISTIC PERSONALITY DISORDER) IN STUDENTS OF GENERAL MEDICINE STUDY PROGRAM IN MALAHAYATI UNIVERSITY Background: High self-esteem becomes a problem when it turns into narcissism or when a person feels his/her self-esteem is high. The effects of narcissism can be problems when they are not mitigated properly into becoming narcistic personality disorder. A presurvey to 10 students showed that 4 (40%) had narcistic symptom tendencies, and 6 (60%) were not narcistic. 4 (40%) had tendencies for higher self-esteem, 4 (40%) had lower tendencies for self-esteem, and 2 (20%) had normal self-esteem and there are 4 victims of cyber bulliying.  Objective: The objective of this research was to find out the correlation of self-esteem to narcistic symptom (narcistic personality disorder) in students of general medicine study program in Malahayati University in 2019.Method: This was a quantitative research by using cross sectional approach. Population was 1,047 general medicine students from academic year 2015 to 2018. 290 respondents were taken by using accidental sampling. Data were collected by using questionnaires and analyzed by using univariate analysis with frequency distribution test and bivariate analysis with chi square test.    Result: The frequency distribution of narcissistic respondents is 55.2%. The frequency distribution of respondents had high self-esteem as many as 54.1%, with p value 0.001 OR 2.3.Conclusion: There was a correlation of self-esteem to narcistic symptom (narcistic personality disorder) in students of general medicine study program in Malahayati University in 2019. The researcher suggests students not being too proud when receiving praises and they should be able to receive criticism from other people in the social media or from the environment. Special guidance are expected especially concerning motivation from lecturers and students affair department to improve student’s self-esteem.Keywords      : Self-esteem, Narcissistic INTISARI: HUBUNGAN HARGA DIRI DENGAN GEJALA NARSISTIK (NARCISSTIC PERSONALITY DISORDER)PADA MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTERUNIVERSITAS MALAHAYATITAHUN 2019 Latar Belakang:Harga diri yang tinggi menjadi masalah saat berubah menjadi narsisme atau rasa harga dirinya tinggi. Dampak gejala narsistik menjadi permasalahan bila tidak ditanggulangi dengan baik akan menjadi gangguan kepribadian narsistik. Hasil presurvey 40% memiliki kecenderungan gejala nasrisitik, 40% memiliki kecenderungan harga diri tinggi serta didapatkan 4 korban cyber bulliying.Tujuan: Diketahui hubungan harga diri dengan gejala narsistik (narcisstic personality disorder) pada mahasiswa Program Studi Pendidikan Dokter Universitas Malahayati Tahun 2019.Metode: Jenis penelitian kuantitatif, menggunakan pendekatan cross sectional. Populasi penelitian ini seluruh mahasiswa kedokteran angkatan 2015-2018 sejumlah 1.047 orang. Sampel 290 responden dengan tehnik accidental sampling. Tehnik pengumpulan data menggunakan kuesioner, uji statistik univariat menggunakan uji distribusi frekuensi dan uji statistik bivariat menggunakan uji Chi Square.Hasil:Distribusi frekuensi responden narsistik 55,2%, memiliki harga diri yang tinggi 54,1%, dengan p value 0,001 OR 2,3.Kesimpulan: Ada hubungan harga diri dengan gejala narsistik (narcisstic personality disorder) pada mahasiswa Program Studi Pendidikan Dokter Universitas Malahayati Tahun 2019. Saran kepada mahasiswa untuk tidak mudah besar hati bila mendapat pujian serta mampu menerima kritikan dari orang lain di media sosial atau lingkungan dan diharapkan adanya bimbingan khusus serta motivasi dari pihak dosen maupun bagian kemahasiswaan untuk meningkatkan harga diri mahasiswa.Kata Kunci:Harga Diri,Narsistik